Multi-hospital surveillance and antibiotic sensitivity among bacterial isolates of acute respiratory and enteric infection in underfive children in Dhaka, Bangladesh - Rahat, Asifuzzaman (BRAC University, 2019)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2015.